Dynamic Calculation of Water Sweep Efficiency and Relative Permeability Curve on Water Drive Reservoir - Liu, Chen; Zhou, Wensheng; Jiang, Junzhe (Frontiers in Energy Research, 2022)
The water sweep efficiency is an important parameter in oilfield development. The present method needs to fit the core relative permeability curve, which has the problem of low accuracy and poor practicability. Based on three kinds of calculation formulas of water saturation, the calculation method of limit water sweep efficiency is put forward, and the dynamic method of two parameters in the index relationship between oil-water relative permeability ratio and water saturation is established. On this basis, the dynamic calculation method of sweep efficiency, oil displacement efficiency and oil-water relative permeability curve is formed, which overcomes the dependence on core permeability curve. The Xijiang oilfield calculation shows that for the south china sea marine sandstone oil field with abundant side water, the oil production is mainly from the water flooding region expansion in the initial oilfield developed period and then change to enhance oil displacement efficiency as the water sweep efficiency is to be stable, so the development policy of this oilfield should be to perfect production patterns nets in the initial oilfield developed period, then be to installe larger pumps and increase liquid production in the middle-later developed period. The proposed method is featured with accessible date, convenient calculation, showing a broad application prospect in dynamic analysis and development effect evaluation of oilfield.